(untitled) (Kindle, 2024)
Artificial intelligence (AI) and deep learning have emerged as powerful tools in understanding the etiology and pathogenesis of cancers. These technologies help uncover complex patterns in large datasets, offering insights into the genetic, environmental, and molecular factors that drive cancer development. By analyzing genomic and multi-omic data, AI can identify mutations, epigenetic changes, and signaling pathway disruptions that contribute to the onset and progression of various cancers. Deep learning models, particularly convolutional neural networks (CNNs), are adept at analyzing medical images, aiding in early cancer detection and diagnosis. They can detect subtle changes in tissue morphology, which helps differentiate between benign and malignant tumors. Moreover, AI can integrate genomic data with clinical information to predict disease progression and treatment outcomes, offering personalized therapeutic approaches. In the study of cancer pathogenesis, AI-driven models can simulate tumor growth and metastasis by mapping interactions within the tumor microenvironment, which includes immune cells, blood vessels, and extracellular matrix components. This allows researchers to explore how cancers evolve, invade, and resist therapies. Overall, AI and deep learning play a transformative role in cancer research, enhancing our understanding of cancer biology, improving early detection, and guiding the development of targeted therapies that can potentially improve patient outcomes.